Correlations between glycaemic control and serum chromium levels among type 2 diabetic patients in Denpasar, Bali - Ascobat, Purwantyastuti (2020)
The National Basic Health Research (Riskesdas) in 2013 showed 6.9% diabetes prevalence in Indonesia with the highest among aged 55 years and above in urban areas. Poor glycaemic control is reported to be related to low chromium levels in type 2 diabetes mellitus (T2DM). This study aimed to determine the correlation between serum chromium and glycaemic control in T2DM patients. Methods: A cross-sectional study was conducted at six community health centres (Puskesmas) in Denpasar, Bali in July 2015-Jan 2016. A total of 165 T2DM patients who met the inclusion criteria were included. The subjects were aged 50-70 years, registered in the Chronic Diseases Management Programme (Prolanis), members of diabetic health clubs in the Puskesmas, and were taking oral hypoglycaemic medication. Anthropometric measurements were taken, including weight, height and waist circumference. Fasting blood samples were collected for determination of glycated haemoglobin (HbA1c) using HPLC, blood glucose (FBG) by tipyrine (GODPAP) enzymatic colorimetric method, and serum chromium using atomic absorption spectrophotometry (AAS). Correlations between HbA1c and FBG with serum chromium were determined using Spearman Correlation test (95% CI). Results: There was a significant negative correlation between FBG levels and serum chromium (r=-0.813; p<0.001); while no significant correlation was found between HbA1c and serum chromium (r=-0.059; p>0.05). Conclusion: Serum chromium levels of T2DM patients in this study were low, while their FBG levels correlated negatively with serum chromium status. Studies on a larger sample of T2DM patients should be undertaken to verify this finding for nutritional care of diabetic patients.